New and Effective Treatment of Experimentally Induced Venous Thrombosis with Anti-inflammatory rPSGL-Ig - Myers, Daniel; Wrobleski, Shirley; Londy, Frank; Fex, Beverly; Hawley, Angela; Schaub, Robert; Greenfield, Lazar; Wakefield, Thomas (Thrombosis and Haemostasis, 2002)
P-selectin antagonism decreases thrombosis and inflammation in animal models of venous thrombosis (VT) prophylaxis. This study defines results using a P-selectin receptor antagonist for VT treatment.Eight juvenile baboons underwent 6 h of iliofemoral venous stasis to produce an occlusive VT. Two days later, animals were treated for 14 days with rPSGL-Ig, 4 mg/kg (n3), LMWH (n2) or saline (n3) and treatment continued weekly (rPSGL-Ig) or daily (LMWH, saline). The animals were examined and sacrificed 14 days after treatment initiation (n4) or on day 90 (n4).Percent spontaneous vein reopening revealed a significant increase (p <0.05) in the proximal iliac vein in rPSGL-Ig and LMWH animals compared to controls (62%, 70% vs 8%), without differences in inflammation. No anticoagulation, thrombocytopenia, or wound complications were found in rPSGL-Ig animals. At 90 days, recanalization with iliac vein valve competence was found in treated animals.rPSGLIg successfully treated established VT without anticoagulation.
Keywords: Venous thrombosis; rPSGL-Ig; P-selectin; inflammation; recanalization